Submissions and future teachers’ association regarding the basic concepts of the sphere of physical culture and sports - Tomenko, O.A.; Cherednichenko, S.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of the work is to determine the characteristics of concepts and associations in relation to the basic concepts of the sphere of physical culture and sports in the future teachers of physical culture. In a questionnaire survey was conducted among 323 students (203 girls and 120 boys aged 17 to 23 years). The possibilities of the formation of students' motives for self-improvement and professional sports and recreational activities. Shows the structure of the students' ideas about the main sphere of physical culture and sports. It was determined that the structure of the students' characterized by a broad spectrum. Found that 14 - 22% of the students physical education is associated with the learning object. Indicator definitions of physical exercise as a form of organization of movements in students of all courses is increasing from 24.4% in the first year to 27.1% in the fourth. Almost half of the respondents believe that training - this kind of activity. Found that a significant number of students do not have a clear understanding of the basic concepts of the theory of physical education.